Hands are not for hitting - Agassi, Martine, 1966-; Heinlen, Marieka (Minneapolis, Minn. : Free Spirit Pub., 2000)
Demonstrates that "hands are not for hitting" by suggesting many positive uses for them, such as saying hello, playing, creating, and helping.
Keywords: School violence -- Prevention -- Juvenile literature; Anger -- Juvenile literature; Hand -- Juvenile literature; Early childhood education -- Activity programs -- Juvenile literature; Behavior; Anger; Violence